PENINGKATAN KETERAMPILAN DAN PENGETAHUAN MAHASISWA MELALUI PROGAM INTERNSHIP TERHADAP EFEKTIVITAS PELAYANAN KEUANGAN KEPADA ANGGOTA PADA KOPERASI CREDIT UNION BONAVENTURA - Desnia Desnia; Dedy Dedy (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
The internship program is a form of practice-based learning that plays a crucial role in enhancing students’ skills and knowledge through real-world work experience, particularly in the field of credit union financial management. Through this program, students gain the opportunity to apply what they have learned in a real-world work setting, thereby strengthening technical skills such as financial administration, the use of financial systems, financial record-keeping, and customer service skills. In addition to technical skills, the internship program also plays a role in improving students’ non-technical abilities, such as communication skills, a sense of responsibility, discipline, work ethic and neatness, teamwork, punctuality, the ability to quickly grasp information, openness to learning new things, integrity and adherence to work ethics, as well as adaptability. Progress in these skills and knowledge is a key element in supporting the effectiveness of financial services, particularly within cooperative organizations like Credit Union Bonaventura, which focuses on member service. The effectiveness of financial services can be measured by the quality of service provided, including speed, accuracy, and the ability to meet members’ needs in a professional and responsive manner. Therefore, internship programs are not only beneficial for developing students’ skills but can also improve the quality of financial services for members. This demonstrates that the skills and knowledge students gain during their internships play a crucial role in delivering effective and high-quality services.